2009
DOI: 10.1002/sim.3637
|View full text |Cite
|
Sign up to set email alerts
|

A statistical model for the dependence between progression‐free survival and overall survival

Abstract: Among the surrogate endpoints for overall survival (OS) in oncology trials, progression-free survival (PFS) is more and more taking the leading role. Although there have been some empirical investigations on the dependence structure between OS and PFS (in particular between the median OS and the median PFS), statistical models are almost non-existing. This paper aims at filling this gap by introducing an easy-to-handle model based on exponential time-to-event distributions that describe the dependence structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
83
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(88 citation statements)
references
References 25 publications
(25 reference statements)
2
83
0
3
Order By: Relevance
“…In recent years, biostatisticians have proposed a wide variety of measures for validating surrogate endpoints [20,21]. Although tumor response and PFS are potential surrogate endpoints for OS in extensive-stage small cell lung cancer [22], their validity is controversial in advanced NSCLC [23].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, biostatisticians have proposed a wide variety of measures for validating surrogate endpoints [20,21]. Although tumor response and PFS are potential surrogate endpoints for OS in extensive-stage small cell lung cancer [22], their validity is controversial in advanced NSCLC [23].…”
Section: Discussionmentioning
confidence: 99%
“…The validity of surrogate endpoints has been determined by previous meta-analyses (18,19). Biostatisticians have also proposed measures for validating surrogate endpoints (20,21). Tumor response and PFS are potential surrogate endpoints for OS in extensive-stage small-cell lung cancer (22), although their validity in advanced NSCLC is controversial (23).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, biostatisticians have proposed various measures for validating surrogate end points [32,33]. Broglio and Berry [2 ]recently reported that the duration of PPS, which they termed survival post-progression (defined as OS minus PFS), was important for determining the applicability of OS as a measure of patient outcome.…”
Section: Discussionmentioning
confidence: 99%